Evaluation of Oral Stereognosis in Relation to Tactile Ability and Patient Satisfaction - Ikbal, Leblebicioglu Kurtulus; Kerem, Kilic; Ravza, Eraslan; Damla, Unlu; Ahmet, Caliskan; Bulent, Kesim; Stephan, Eitner (The Journal of oral implantology, 2017)
We investigated the oral stereognostic ability (OSA) of dentate individuals, conventional complete denture patients, and maxillary implant-supported denture patients with bar attachments. Stereognosis tests were carried out, and the relationship between OSA and patient satisfaction was assessed with a satisfaction survey: the Turkish version of the oral health impact profile-14 (OHIP-TR-14). To compare differences in oral sensory function among individuals with natural dentition, complete denture wearers, and maxillary implant-supported denture wearers, tactile awareness (thickness perception threshold) and pressure awareness (threshold of lateral loading) were assessed. According to the results, the oral perception level of natural dentate patients was higher than that of the complete denture group and maxillary implant-supported complete denture group at the end of the study. There was no statistically significant difference in OHIP-TR-14 scores between the maxillary implant-supported complete denture group and the complete denture group ( P < .05). The control group perceived the applied lateral and vertical forces statistically earlier than the other groups ( P < .001). There was no statistically significant difference between the complete denture and maxillary implant-supported denture groups in terms of the lateral pressure threshold or thickness tactile threshold ( P > .05). At the end of the study it was concluded that there was no correlation between oral perception levels and satisfaction in patients with complete dentures and patients with maxillary implant-supported complete dentures. The control group, compared with the complete denture and maxillary implant-supported complete denture groups, perceived the lateral and vertical forces statistically earlier than the other groups.
EVALuna2:35442